2021
DOI: 10.1530/rep-20-0531
|View full text |Cite
|
Sign up to set email alerts
|

Formation of fibrin at sites of conceptus adhesion in the ewe

Abstract: In ruminants, various molecules are involved in regulating conceptus attachment and adhesion; however, molecules that maintain the conceptus adhesion have not been well characterized. We hypothesized that conceptus must produce a molecule(s), yet uncharacterized or overlooked, which maintain conceptus adhesion to the uterine epithelium. In this study, we aimed to identify new candidate(s) in conceptus secretory proteins responsible for maintaining conceptus adhesion in sheep. We performed RNA-sequence analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…From our previous RNA-sequencing data [ 14 ], EMT-related transcripts were extracted, their expression was evaluated, and heatmap analysis was performed. The heatmap analysis revealed that transcripts encoding EMT-related genes were distinctively upregulated in P21 ovine conceptuses ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From our previous RNA-sequencing data [ 14 ], EMT-related transcripts were extracted, their expression was evaluated, and heatmap analysis was performed. The heatmap analysis revealed that transcripts encoding EMT-related genes were distinctively upregulated in P21 ovine conceptuses ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… ). These analyses indicated that the increase in EMT-related transcripts and conceptus adhesion appeared to occur simultaneously in ovine conceptuses on P21 [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations